Onco‐testicular sperm extraction: birth of a healthy baby after fertility preservation in synchronous bilateral testicular cancer and azoospermia. (20th May 2014) - Roque, M.; Sampaio, M.; de Oliveira Salles, P. G.; Geber, S.
Summary Testicular germ cell tumours (TGCT) represent 1%–1.5% of all male neoplasms, and they have the highest prevalence among men between 15 and 35 years old. Synchronous bilateral disease is a rare presentation, and the ratio of metachronous to synchronous bilateral disease is about 4 : 1. Several studies have suggested a correlation between male infertility and testicular cancer, with a 20‐fold increase in the incidence of testicular cancer in infertile patients compared with the general population. At the time of diagnosis, 50%–75% of patients with unilateral TGCT present with subfertility; almost 13% of the patients are azoospermic before treatment, and up to two‐thirds of patients become azoospermic following adjuvant cancer therapies. Therefore, fertility preservation should be considered in all oncological treatments. The only available option to preserve the reproductive potential in azoospermic patients with testicular cancer is to perform an onco‐testicular sperm extraction (onco‐TESE) before cancer treatment. In this paper, we describe a rare case of a patient with synchronous bilateral testicular cancer and azoospermia who was submitted to onco‐TESE, sperm cryopreservation, and which was followed by the delivery of a healthy baby after intracytoplasmic sperm injection (ICSI), emphasising the importance of fertility preservation in oncology patients.